Metode Participatory Action Research dalam Pemberdayaan Pengrajin Batik Berbasis Budaya Lokal - Samsinas, Samsinas; Haekal, Ahmad (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2023)
This article specifically examines how the Participatory Action Research (PAR) method is applied in empowering local culture-based batik craftsmen in Kamonji Village, West Palu District, Palu City. In applying the PAR method, several techniques are used, including: observation, focus group discussion (FGD), sharing knowledge, in-depth interviews, training, and documentation. In the FGD, the batik craftsman community, as well as participants, can critique their social conditions, making them aware of the problems, needs, potential, and efforts to solve them in a participatory manner with the parties involved in the transformation effort. FGD participants recommended holding printed batik-making training activities to strengthen batik-making skills. This is considered more effective, efficient, and economically profitable compared to woven batik. Additionally, it can meet the need for developing local culture-based souvenirs in Palu City. This recommendation was followed up with training in making printed batik and sharing follow-up plans.